The Representation of Multicultural Content Provided by “World-Class Franchise” English Course Textbook Used in Indonesia: A Critical Discourse Analysis Study - Alawlaqi, Salma Ali Salem Mansoor; Dihliza Basya (International Journal of Language and Literary Studies, 2023)
Multicultural values in English as a Foreign Language (EFL) textbooks have attracted many researchers, academics, and educators in many studies around the world. However, there is limited literature examining the representation of multicultural content in English course textbooks used in Indonesia, specifically EFL course textbooks from world-class franchise programs. Therefore, this study employs Critical Discourse Analysis (CDA) to examine the impartiality of cultural content representation provided by the EFL course textbook regarding different cultures and ethnic groups. This study provided Halliday’s systemic functional analysis to examine verbal data. While Kress and Van Leeuwen’s visual grammar theory was employed to comprehend, analyze, and explore visual representations from selected EFL course textbooks. This study reveals the EFL course textbook does not reflect the diversity of cultures in Indonesia, as it mainly focuses on the perspectives and traditions of Western and European countries. This creates an unfair and distorted representation of other cultures, especially those from Asia, Africa, and the Middle East, whose values and beliefs are not adequately considered or respected within the EFL course textbook. The implications of this study suggest that the inclusion of cultural sensitivity within EFL course textbooks is crucial in fostering cultural awareness, promoting respect among EFL learners, and creating a more equitable and inclusive learning environment.